2018
DOI: 10.3758/s13428-018-1067-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic models of choice

Abstract: Parameter estimation in evidence-accumulation models of choice response times is demanding of both the data and the user. We outline how to fit evidence-accumulation models using the flexible, open-source, R-based Dynamic Models of Choice (DMC) software. DMC provides a hands-on introduction to the Bayesian implementation of two popular evidence-accumulation models: the diffusion decision model (DDM) and the linear ballistic accumulator (LBA). It enables individual and hierarchical estimation, as well as assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
219
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(220 citation statements)
references
References 63 publications
1
219
0
Order By: Relevance
“…We used the Dynamic Models of Choice (DMC; Heathcote et al, 2018) software implemented in R (R Core Team, 2018) to estimate model parameters via Bayesian hierarchical modelling. In hierarchical modelling, the population-level mean and standard deviation parameters characterise the population-level distribution for each model parameter.…”
Section: Modelling Of Response Inhibition the Ex-gaussian Distributimentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Dynamic Models of Choice (DMC; Heathcote et al, 2018) software implemented in R (R Core Team, 2018) to estimate model parameters via Bayesian hierarchical modelling. In hierarchical modelling, the population-level mean and standard deviation parameters characterise the population-level distribution for each model parameter.…”
Section: Modelling Of Response Inhibition the Ex-gaussian Distributimentioning
confidence: 99%
“…Weakly informative uniform priors were set for the population-level parameters, which are identical to those of Skippen et al (2019). Posterior distributions of the parameters were obtained using Differential Evolution Markov Chain Monte Carlo (MCMC) sampling (Ter Braak, 2006), with steps closely mimicking Heathcote et al (2018).…”
Section: Modelling Of Response Inhibition the Ex-gaussian Distributimentioning
confidence: 99%
“…As many evidence-accumulation models have analytic likelihoods, and so are amenable to MCMC methods for obtaining posterior distributions, Warp-III sampling is not limited to the LBA, but may be readily applied to other models, such as the diffusion decision model (DDM; Ratcliff, 1978;Ratcliff & McKoon, 2008). Heathcote et al's (2018) DMC software enables the hierarchical MCMC-based estimation of not only the LBA and the DDM, but also a variety of other models including single-boundary and racing diffusion models (Leite & Ratcliff, 2010;Logan, Van Zandt, Verbruggen, & Wagenmakers, 2014), lognormal race models (Heathcote & Love, 2012;Rouder, Province, Morey, Gómez, & Heathcote, 2015), as well as race models of the stop-signal paradigm (Matzke et al, 2013;Matzke, Love, & Heathcote, 2017). Our easyto-use R-implementation of the Warp-III sampler enables the computation of the marginal likelihood of any model implemented in the DMC software.…”
Section: Discussionmentioning
confidence: 99%
“…The priors in Eq. 8 were taken from Heathcote et al (2018). Although we believe that these priors provide a reasonable setup based on our experience with the LBA parameter ranges, they may be replaced by empirically informed priors in future applications.…”
Section: Prior Distributionsmentioning
confidence: 99%
“…We found that TIDE provided an approximation of the marginal likelihood that closely matched TI for models with a single subjects. However, when extending the models hierarchically, we found that certain assumptions about the dependence between the individual and group level parameter samples resulted in large differences in the TI approximated marginal likelihood, where the standard dependent sampling results in higher marginal likelihoods than the recently implemented (e.g., Heathcote et al, 2018; implemented within their DMC package) independent sampling. We extended TIDE to these two different situations, with dependent sampling only requiring a natural extension of TIDE, and independent sampling adding the use of past iterations in a manner similar to "Z updating" from an extension of DE-MCMC, DE-MCz (ter Braak & Vrugt, 2008).…”
Section: Introductionmentioning
confidence: 90%